IQSEC2-related encephalopathy in male children: Novel mutations and phenotypes - Liu, Xinting; Zhang, Shan; Wan, Lin; Zhang, Xiaoli; Wang, Haiping; Zhang, Hongwei; Zhu, Gang; Liang, Yan; Yan, Huimin; Zhang, Bo; Yang, Guang (Frontiers in Molecular Neuroscience, 2022)
The isoleucine–glutamine (IQ) motif and Sec7 domain-containing protein 2 (IQSEC2) gene, located at Xp11. 2, are associated with nervous system diseases, such as epilepsy, autism, and intellectual disabilities. Gender-related differences in the severity of phenotype severity have been described previously. Here, we report the details of seven male children with IQSEC2 mutations from different families. During this investigation, we explored the relationship between the genotype and phenotype of IQSEC2 mutations; to do so, we recruited seven children with pathogenic/likely pathogenic IQSEC2 mutations who were diagnosed with global developmental delay and/or epilepsy. Their clinical features were assessed, and Trio-based whole-exome sequencing (trio WES) was conducted in seven pedigrees. A variety of algorithms and computational tools were used to calculate the pathogenicity, protein stability, conservation, side chain properties, and protein-protein interactions of mutated proteins. The seven patients ranged in age from 18 months to 5 years. Among them, six children were found to have both developmental delay and epilepsy, and one child only exhibited developmental delay. Four novel mutations (c.316C > T, c.443_4 44dup, c.3235T > C, and c.1417G > T) were newly reported. Two patients did not have truncated aberrant proteins caused by missense mutations. Still, they did have severe phenotypes, such as early-onset epilepsy in infancy, because the mutations were located in domains like the pleckstrin homology and IQ calmodulin-binding motif domains. The bioinformatics analysis also proved that missense mutations may be located in the functional region, which affects protein stability and is harmful. In summary, severe phenotypes, such as early-onset epilepsy in infancy, occur in male patients with a missense mutation in specific domains (e.g., pleckstrin homology and IQ calmodulin-binding motif domains). Some female individuals with IQSEC2 mutations may be asymptomatic because of the skewed inactivation of the X chromosome.